Proliferating Myositis: An Inflammatory Lesion often Misdiagnosed as A Malignant Tumor - Binesh Fariba; Sobhanardekani Mohammad; Zabihi Somayeh; Behniafard Nasim (Sciendo, 2016)
Proliferative myositis (PM) is a rare inflammatory disease. Most commonly, the lesion occurs in the extremities. Regarding its fast growth and bizarre shape of the cellular components this entity commonly misdiagnosed and the patients undergo improper therapeutic approaches. In other words, it is often misdiagnosed as sarcoma. The diagnosis can only be made by the microscopic examination, so biopsy is mandatory. Here the authors report a patient with PM who was initially misdiagnosed as pleomorphic sarcoma of the lower extremity and explain this rare entity.